2022
DOI: 10.1007/s00148-021-00882-x
|View full text |Cite
|
Sign up to set email alerts
|

Reopening schools in a context of low COVID-19 contagion: consequences for teachers, students and their parents

Abstract: Knowing how school reopenings affect the spread of COVID-19 is crucial when balancing children’s right to schooling with contagion management. This paper considers the effects on COVID-19 testing prevalence and the positive test rate of reopening Norwegian schools after a 6-week closure aimed at reducing contagion. We estimate the effects of school reopening on teachers, parents and students using an event study/difference-in-differences design that incorporates comparison groups with minimal exposure to in-pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In addition, it was important to strengthen students’ readiness to go on site, encourage them to discuss COVID-19-prevention issues with family or friends, and reduce their fear of infection. In comparison with other studies on schooling hesitancy [ 7 , 40 ], this study supported that students’ belief and their surroundings remained important determinants. Regarding the consequences of online studying, students’ mental health could help to identify those unsuited for online learning who need continuous monitoring and additional support if the reopening is postponed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, it was important to strengthen students’ readiness to go on site, encourage them to discuss COVID-19-prevention issues with family or friends, and reduce their fear of infection. In comparison with other studies on schooling hesitancy [ 7 , 40 ], this study supported that students’ belief and their surroundings remained important determinants. Regarding the consequences of online studying, students’ mental health could help to identify those unsuited for online learning who need continuous monitoring and additional support if the reopening is postponed.…”
Section: Discussionsupporting
confidence: 80%
“…This was conducted to physically separate students and maintain a stable number of COVID-19 infections [ 1 ]. Even though evidence reported that children may not be potential COVID-19 spreaders [ 2 , 3 ], it may have been hard to make a decision about the school reopening because of the effects of the school reopening on disease spread [ 4 ], which depended on the prevalence of COVID-19 infection in each area [ 5 , 6 ], as well as its effects on stakeholders, including teachers, parents, and students [ 7 ]. Focusing on students during the pandemic, students were either a “risk to others” or “people at risk” [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even the several studies conducted a posteriori have not reached a final answer in this regard. Interestingly enough however, some of these studies actually observed that especially when other measures were in place, and particularly in relation to primary schools, little significant increase in COVID-19 cases is detectable in correlation to and in the context of school in person activities (see for example, Bonaccorsi et al, 2021 ; Fukumoto et al, 2021 ; Walsh et al, 2021 ; Godøy et al, 2022 ). Studies also reported that children are less susceptible than adults to COVID-19 infection and, if infected, are significantly less likely than adults to infect others (see Monod et al, 2021 ; Kraaijeveld et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“… [8] in Oslo, Norway found that school closures were equally effective as targeted infection prevention and control measures in open schools in reducing student infection rates. Similarly, other study designs, such as an event-study/difference-in-differences approach, have been used to evaluate the effects of reopening schools [11] , [12] , reporting effects on the population level [11] , [12] to small and transitory effects only in certain subgroups [13] . Concerning the closure of cultural, sport, or leisure intuitions/venues, Barbeito et al in Spain have attempted to estimate the specific effects of various NPIs, including sports and culture activities, but their results for NPIs targeting culture, leisure venues, and indoor sports were inconsistent.…”
Section: Discussionmentioning
confidence: 99%